Identification of Novel GCK and HNF4α Gene Variants in Japanese Pediatric Patients with Onset of Diabetes before 17 Years of Age - Rumi Katashima; Mari Matsumoto; Yuka Watanabe; Maki Moritani; Ichiro Yokota (Journal of Diabetes Research)
Background. Maturity-onset diabetes of the young (MODY) is commonly misdiagnosed as type 1 or type 2 diabetes. Common reasons for misdiagnosis are related to limitations in genetic testing. A precise molecular diagnosis is essential for the optimal treatment of patients and allows for early diagnosis of their asymptomatic family members. Objective. The aim of this study was to identify rare monogenic variants of common MODY genes in Japanese pediatric patients. Methods. We investigated 45 Japanese pediatric patients based on the following clinical criteria: development of diabetes before 17 years of age, a family history of diabetes, testing negative for glutamate decarboxylase-65 (GAD 65) antibodies and insulinoma-2-associated autoantibodies (IA-2A), no significant obesity, and evidence of endogenous insulin production. Genetic screening for MODY1 (HNF4α), MODY2 (GCK), MODY3 (HNF1α), and MODY5 (HNF1β) was performed by direct sequencing followed by multiplex ligation amplification assays. Results. We identified 22 missense variants (3 novel variants) in 27 patients (60.0%) in the GCK, HNF4α, and HNF1α genes. We also detected a whole exon deletion in the HNF1β gene and an exon 5–6 aberration in the GCK gene, each in one proband (4.4%). There were a total of 29 variations (64.4%), giving a relative frequency of 53.3% (24/45) for GCK, 2.2% (1/45) for HNF4α, 6.7% (3/45) for HNF1α, and 2.2% (1/45) for HNF1β genes. Conclusions. Clinicians should consider collecting and assessing detailed clinical information, especially regarding GCK gene variants, in young antibody-negative patients with diabetes. Correct molecular diagnosis of MODY better predicts the clinical course of diabetes and facilitates individualized management.